2015
DOI: 10.4049/jimmunol.1401930
|View full text |Cite
|
Sign up to set email alerts
|

Unique Roles of Infiltrating Myeloid Cells in the Murine Uterus during Early to Midpregnancy

Abstract: Leukocyte infiltration into the uterus is a characteristic feature in early to midpregnancy, but the composition and function of these leukocytes are not well understood. Using a pregnant murine model, we showed that myeloid cells and uterine NK (uNK) cells were the predominant populations in uteri during early to midgestation, whereas T and B cells were constrained. Uterine myeloid populations included cells that infiltrated from the circulation (myeloid-derived suppressor cells [MDSCs], monocyte-derived macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 63 publications
(77 reference statements)
7
72
0
1
Order By: Relevance
“…These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37). Taken together, our results add new aspects of MDSC biology in human pregnancy as being crucial during physiological conditions, that is, in human pregnancy, and point again toward a role for GRMDSCs in protecting the fetus from immune rejection.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37). Taken together, our results add new aspects of MDSC biology in human pregnancy as being crucial during physiological conditions, that is, in human pregnancy, and point again toward a role for GRMDSCs in protecting the fetus from immune rejection.…”
Section: Discussionsupporting
confidence: 78%
“…CXCL12, the ligand for CXCR4, has been shown to be expressed by trophoblast and decidual stromal cells and to be responsible for homing of decidual NK cells (42,43). Recently, Zhao et al (37) showed an association of an upregulation of CXCL12 and an accumulation of MDSCs in the pregnant mouse uterus. Moreover, GR-MDSCs in CF patients were recently shown to express CXCR4 (16).…”
Section: Discussionmentioning
confidence: 98%
“…Macrophages can be identified by the expression of surface markers such as CD14 and CD11b (Houser et al, 2011; Zhao et al, 2015). Houser et al used CD14, CD11b, and CD11c to characterize macrophages in first trimester human decidua.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that dendritic cells (DCs) (9)(10)(11)(12) and regulatory T cells (Tregs) (13)(14)(15) are crucial for the establishment and maintenance of pregnancy. For instance, Plaks et al (10) demonstrated that the depletion of DCs causes a failure of embryo implantation in mice, and the depletion of Tregs induces implantation failure and increases resorption in allogeneic, but not in syngeneic, mice (14).…”
mentioning
confidence: 99%